A Client-Server and Web-Based Graphical User Interface Design for the Mathematical Model of Cardiovascular-Respiratory System. (5th May 2021) - Bizimungu, Theogene; Harelimana, Domonique; Marie Ntaganda, Jean
Abstract : The prediction of cardiac conditions can be done through comparison and analysis of parameters transformed into mathematical model equations. This paper aims to present the design of a web-based graphical user interface of mathematical model of cardiovascular-respiratory system (ICRSMM) as an appropriate displaying tool. The designed system offers an easy way of recording and storing parameters in a database. Those parameters are computerized to generate automatic results in a graphic representation, which is an effective way used in medicine to allow physicians, nurses, and other experienced health personnel to analyze and discuss results. The designed solution provides an adequate and friendly environment that eases the task of recording the results in a graphic representation. This gives a clear picture of analysis to determine a healthy or unhealthy cardiovascular-respiratory system of a person exercising. However, such a complex design solution comes in to put an accent of consideration to an area of research that still needs more discoveries and exploration.